Penggunaan Gadget dan Perubahan Sosial Budaya pada Usia Produktif - Maman Wijaya; Arief Rachman Hakim; Vini Kartika Rachmawati (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2021)
The use of gadgets is very massive in every age range in every region. It is not known with certainty what habits have been forgotten, what cultures have changed, and at what ages experienced these changes. This descriptive analysis study aims to examine the use of gadgets and their relationship to changes in the sociocultural of respondents who are grouped by age. Sociocultural change is based on Weberian Theory. The method used a survey with questionnaire instrument arranged in google form which is distributed through the WhatsApp application for 2×24 hours and received 197 respondents. The data is processed by IBB SPSS Statistics Data Editor. Data processing includes the frequency, distribution, and trend of the data, as well as for several variables, the correlation is calculated at the 95% confidence level. The results show that the use of gadgets changes people's habits, both young and old. Several old habits are forgotten with the emergence of several new habits. Old habits that are forgotten and new habits that emergence are not significantly related to age but have a significant relationship with how to function gadgets as work tools and business tools with correlation coefficients about 0.77 and 0.42. Objects of cultural development such as oral traditions, manuscripts, and traditional games are relatively unfamiliar, especially in the age range of 20–40 years. Thus, the changes in the respondent's sociocultural are related to the use of gadgets.